Neutral lipid production from hydrocarbon-contaminated cork sorbents using Rhodococcus opacus B4 - Castro, Rita (2017)
Portuguese Science Foundation and European Social Fund through the grant SFRH/BD/64500/2009, the projects UID/BIO/04469/2013, COMPETE 2020 (POCI -01-0145-FEDER-006684); RECI/BBB-EBI/0179/2012 (FCOMP-01-0124-FEDER- 027462) and BioTecNorte operation (NORTE-01-0145-FEDER-000004). The authors gratefully acknowledge Cortiçeira Amorim, S.A., Portugal, for providing the CORKSORB materials used in this work